Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1136/bjsports-2011-090724
|View full text |Cite
|
Sign up to set email alerts
|

Fitness levels and physical activity among class A drug users entering prison

Abstract: Many class A drug users entering prison had high levels of fitness and physical activity before admission, often gained from walking. Walking activity reduced when they entered prison, posing a challenge to maintaining healthy activity levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
1
11
0
1
Order By: Relevance
“…Despite this consensus, people with harmful substance use issues typically report far lower rates of exercise than the general population [8]. This is true for out-of-treatment users, inpatients [16,17], and outpatients [16], with mixed evidence from inmates [18,19]. Substance use disorders are the most common mental disorders among inmates, with pooled estimates of a 51% prevalence of drug use disorders worldwide, and a 24% prevalence of alcohol use disorder [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this consensus, people with harmful substance use issues typically report far lower rates of exercise than the general population [8]. This is true for out-of-treatment users, inpatients [16,17], and outpatients [16], with mixed evidence from inmates [18,19]. Substance use disorders are the most common mental disorders among inmates, with pooled estimates of a 51% prevalence of drug use disorders worldwide, and a 24% prevalence of alcohol use disorder [20].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have examined inmates’ capacities to adopt exercise without interventions. Substance users in the UK reported reductions in physical activity during the first week of incarceration [19], while cross-sectional studies from Italy and Nigeria found both positive and negative relationships, respectively, between exercise frequency and length of incarceration [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of participants reported a reduction in physical activity levels on reception into prison and such findings concur with a study of UK drug-using prisoners in which aerobic physical activity reduced by a factor of >2.5 following reception into prison. 28…”
Section: Discussionmentioning
confidence: 99%
“…Different <<previous research has suggested that physical activity levels change when users enter prison>> (Fischer, 2012). <<The present investigation was contacted to identify the attitudes of Greek prisoners regarding to physical activities and sports and to compare these with age, educational level, prison type, terms of geographical stratification the prisoners who were residents of towns showed negative attitudes in factor PA2 and e) the relationship of prisoners with the sport, showed that participants who declared athletes had positive attitudes in factors PA1.…”
Section: Fig 5 Differences Across Previous Involvement Discussionmentioning
confidence: 99%